2015
DOI: 10.1016/j.jbiomech.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

A clinically relevant BTX-A injection protocol leads to persistent weakness, contractile material loss, and an altered mRNA expression phenotype in rabbit quadriceps muscles

Abstract: Botulinum toxin type-A (BTX-A) injections have become a common treatment modality for patients suffering from muscle spasticity. Despite its benefits, BTX-A treatments have been associated with adverse effects on target muscles. Currently, application of BTX-A is largely based on clinical experience, and research quantifying muscle structure following BTX-A treatment has not been performed systematically. The purpose of this study was to evaluate strength, muscle mass, and contractile material six months follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 37 publications
2
49
1
Order By: Relevance
“…One question that arises after BoNT‐A injection treatment is whether muscle can fully recover to its former state . In the present studies, the VL muscle of the quadriceps complex did not appear to recover at 6 months post‐injection, irrespective of the injection frequency . One set of reasons for this lack of recovery could be the prolonged expression in the injected muscles of molecules, which impeded or interfered with such recovery.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…One question that arises after BoNT‐A injection treatment is whether muscle can fully recover to its former state . In the present studies, the VL muscle of the quadriceps complex did not appear to recover at 6 months post‐injection, irrespective of the injection frequency . One set of reasons for this lack of recovery could be the prolonged expression in the injected muscles of molecules, which impeded or interfered with such recovery.…”
Section: Discussioncontrasting
confidence: 57%
“…In a recent report, it was found that a single BoNT‐A injection into the rabbit quadriceps musculature led to persistent muscle weakness and loss of contractile material, and these alterations did not appear to progress with repeat injections. It was noted that the loss of contractile material was associated with the appearance of fatty infiltration, which would likely lead to the secretion of adipokines, such as adiponectin (APN), adipocyte binding protein 2 (AP2), and leptin …”
mentioning
confidence: 99%
See 3 more Smart Citations